Decent Work and Work Motivation in Lawyers: An empirical research - Ferraro, Tânia (2018)
This study aimed for better understanding of the effect of decent work on work motivation in lawyers in Portugal and Brazil (N = 611). The Decent Work Questionnaire (DWQ) and Multidimensional Work Motivation Scale (MWMS) were applied. The results of analysis of the canonical correlations showed the presence of two operating mechanisms (two significant canonical correlations). They suggest that fulfilling-and-productive-work is associated positively with intrinsic-and-identified-work-motivation and negatively with amotivation. It was also observed that an adequate working-time/workload is negatively associated with material-extrinsic-motivation (such as money). Summarizing, the results suggest that decent work, especially some of its dimensions, has an important role in promoting work motivation through two main mechanisms, the first one called ‘worthy working life as part of being a citizen in society’ and the second one called ‘contextual life comfort and committed effort’. Limitations and practical implications conclude this article.